2013
DOI: 10.1136/bjsports-2013-092734
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sports concussion: an evidence-based systematic review

Abstract: SA and SM contributed equally to this work. AbstractConcussion is a common sports injury with approximately 1.6 -3.8 million sport-related concussions reported in the US annually. Identifying risk factors may assist in preventing these injuries. This systematic review aims to identify such risk factors. Three electronic databases; ScienceDirect, PubMed and SpringerLink, were searched using the keywords "RISK FACTORS" or "PREDISPOSITION" in conjunction with "SPORT" and "CONCUSSION". 2Based on the inclusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
142
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 114 publications
(204 reference statements)
13
142
0
3
Order By: Relevance
“…Whereas helmets do reduce the risk of moderate to severe head injuries, current helmet designs may not prevent concussion. [16][17][18] Furthermore, although our survey found that most curlers believe in a role for helmets, actual use is rare and stigmatized. Faced with similar challenges, other sports have implemented changes to rules to reduce concussions.…”
Section: Discussionmentioning
confidence: 94%
“…Whereas helmets do reduce the risk of moderate to severe head injuries, current helmet designs may not prevent concussion. [16][17][18] Furthermore, although our survey found that most curlers believe in a role for helmets, actual use is rare and stigmatized. Faced with similar challenges, other sports have implemented changes to rules to reduce concussions.…”
Section: Discussionmentioning
confidence: 94%
“…La mise en place de recommandations pour la prévention des SRC achoppe sur l'absence de preuve scientifique quant au rôle joué par chacun de ces facteurs [3,6,[49][50][51]. On note parmi les facteurs de risque avancés dans la littérature : -le genre.…”
Section: Facteurs Influençant La Survenue Et/ou La Gravité D'une Srcunclassified
“…Pre-morbid learning disorders, behavioural issues, or mental health problems are all known to be the source of a number of the post-concussion symptoms and clusters of symptoms [37]. For example, athletes with Attention Deficit Hyperactivity Disorder (ADHD) [38][39][40][41][42] or learning problems [39] have a greater lifetime history of concussion, and individuals with a prior history are at increased risk for a future concussion [43].…”
Section: Clinical Historymentioning
confidence: 99%